Kognitivna rehabilitacija - Čuš, Anja (Rehabilitacija (Ljubljana), 2010)
Acquired brain damage often results in cognitive deficits that can profoundly affect an individualćs daily functioning. Taking into account a variety of factors influencing recovery and through the use of different approaches and techniques cognitive rehabilitation plays a key role in promoting the recoveryof cognitive functions. There are two main approaches in cognitive rehabilitation, the first one being restitutive approach, that aims at restoring the impaired function, and the second one being compensatory approach, through which an individual develops new strategies and adjusts to acquired deficits. In literature the restitutive approach is mentioned mainly in the context of recovery of attention, while compensatory techniques are usually recommended in recovery of memory and executive functions. For mild cognitive deficits compensation is possible through acquiring new mental strategies, while more severe impairments can be managed with the use of external aids. Beside impairment in cognitive functioning acquired brain damage can also affect interpersonal and emotional functioning. Consequently treatment on all three domains is needed in a context of holistic and integrated neuropsychological rehabilitation.
Keywords: Attention; Brain Injuries; Cerebrovascular Disorders; Cerebrovaskularne motnje; Cognition Disorders; Cognitive Therapy; kognitivne sposobnosti; Memory Disorders; možganske okvare; Možganske poškodbe; Pozornost; rehabilitacija; Spomin, motnje; Spoznavne motnje; Spoznavno zdravljenje; therapy; vocational rehabilitation; zdravljenje